Nutrients depictions of Barhi date palm (Phoenix dactylifera L.) kernels - Mahmud, I. A.; Mirghani, Mohamed Elwathig Saeed; Al-Khatib, Ma'an Fahmi Rashid; Yusof, Faridah; Shahbuddin, Munira; Othman, Rashidi; Daoud, Jamal Ibrahim (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Phoenix dactylifera L (Date palm) is one of the oldest known fruit crops in the world, and the consumption of date fruits is no longer restricted to the Middle Eastern countries. Date palm kernels are waste products of date fruit industry which are normally being discarded. Based on their dietary fiber content; date palm kernels (DPK) have been proposed to be used as fiber-based food supplement, caffeine free coffee alternative and animal feed ingredient. Hence, utilization of such waste is highly desirable for the date industry. To accommodate these benefits, and subsequent to some uses associated with DPK, this study sought to investigate the biochemical and nutritional values of the Barhi date palm kernels (BDPK) grown in Iraq. The results show that BDPK is an excellent source of dietary fiber (66.24 g/100g). Glutamic acid was found to be the predominant amino acid, (0.674 g/100g), followed by Arginine and aspartic acid (0.437 g/100g and 0.320 g/100g, respectively). Potassium was the most occurring mineral in BDPK (2.39 g/kg), and the main sugars were sucrose and fructose (0.548 g/100g and 0.249 g/100g, respectively). Gas-liquid chromatography revealed that the main unsaturated fatty acid (USFA) was oleic acid (40.927 mg/100g), while the main saturated fatty acid (SFA) were lauric acid (20.270 mg/100g) and myristic acid (12.288 mg/100g). Furthermore, the BDPK depicted considerable concentrations of vitamins, in which vitamin B5 (40.4 mg/100g) showed the highest value. The results obtained indicate a strong potential for BDPK to be used in human nutrition, cosmetics, and pharmaceutical applications and may provide an important economic advantage through increasing the utilization of BDKP while also additive value will be added to the residue.